Students satisfaction towards the university: Does service quality matters? - Chuah, Chin Wei; Sri Ramalu, Subramaniam (Macrothink Institute, 2011)
This study examines the relationship between service quality (SQ) and the level of student’s satisfaction (SS) using a field study of 100 undergraduate students in one of the university in Malaysia. The findings of this study reveals that SQ is a vital factor that determines the level of SS. Specifically, the result of this study reveals that the better the SQ provided by the university, the higher the level of SS.Responsiveness, assurance, and empathy are the three dimensions of SQ that is significantly related to the level of SS.The findings of this study have made significant contribution to the body of knowledge in student’s satisfaction management in higher education institutions. The findings of this study also made practical implication to management of higher education especially in the area where SQ improvement is needed.